Integrated management of root- knot nematode, meloidogyn incognita(kofoid & white) chiywood in coleus, solenostemon rotundifolius (poir) morton - Nisha M S (Department of Agricultural Entomology, College of Agriculture, 2005)
The root-knot nematode, Meloidogyne incognita (Kofoid and White) Chitwood is a serious pest in coleus, Solenostemon rotundifolius Poir (Morton) causing damage to tubers both in field and storage. A detailed study was undertaken at College of Agriculture, Vellayani during 2002-2005 to evolve an integrated management strategy in coleus. Experiments were carried out to find out the extent of crop loss under micro plot and storage conditions, biochemical changes due to M. incognita infestation in tubers, to identify the varietal resistance and to select effective treatments in nursery (physical methods, bioagents and organic amendments) and main field (bioagents and organic amendments singly and in combination). Crop loss studies conducted under microplot condition indicated that there was significant reduction in biometric characters at monthly intervals from lowest inoculum level of 100 J2 onwards. The yield attributing characters also showed significant reduction at 100 J2 level (15.77 to 19.13 per cent). In the case of nematode population, there was progressive increase in recovery as the initial inoculum level increased from 100 to 5000 J¬¬2. Crop loss studies under storage condition revealed that tubers obtained from 5000 and 1000 J2 inoculated plants started rotting and get deteriorated at 15 and 45 days after storage respectively. The stored tubers from 500 J¬2, 100 J2 and uninoculated plants exhibited a weight loss of 96.50, 86.50 and 12.50 per cent respectively at three months after storage. Germination percentage of tubers collected from 100 and 500 J2 inoculated plants showed 42.37 and 7.47 reduction respectively over the uninoculated at three months after storage. The vigour of the plants in terms of biometric characters also reduced significantly at the lowest inoculum level of 100 J2. The biochemical changes of tubers collected from plants inoculated with different levels of M. incognita revealed significant reduction in starch, sugar and crude fibre content. The percentage reduction being 6.32 to 33.33, 8.06 to 17.47 and 18.99 to 62.03 respectively as the population of nematodes increased from 100 to 5000 J2. However, there was slight increase in protein content from 12.94 to 14.42 per cent. Results on the resistance of coleus varieties/lines/accessions against M. incognita, established that variety Sree Dhara performed better in reducing the multiplication of nematodes in soil, root and tuber and production of root-knots, females, egg masses and eggs per egg mass. However in the case of total, marketable and edible portion weight of tubers, the performance of variety Sree Dhara and Nidhi was statistically on par. Based on the statistical superiority of the variety Sree Dhara to resist nematode infestation and numerically higher yield than Nidhi, Sree Dhara was selected as the resistant variety and included as a component in ensuing integrated nematode management study in coleus. The evaluation of various treatments in the nursery revealed that soil solarization using 150 guage LDPE film for 15 days or application of bioagent viz., Paecilomyces lilacinus or Bacillus macerans @ 30 g m-2 significantly reduced the number of larvae, root-knots and egg masses in root (65.74 to 90.75 per cent reduction over the untreated). The reduction in M. incognita population contributed significant improvement in biometric characters which in turn resulted healthy vigorous cuttings of S. rotundifolius for transplantation. Thus soil solarization and application of either P. lilacinus or B. macerans were selected as nursery treatments for further investigations. Among the main field treatments, application of P. lilacinus (15 g m-2) in combination with either neem cake (100 g m-2) or B. macerans (15 g m-2) significantly reduced M. incognita population and improved the biometric characters, yield and quality parameters of S. rotundifolius. The treatment combinations, P. lilacinus + neem cake and P. lilacinus + B. macerans showed 81.42 and 71.58 per cent increase respectively in total weight of tubers when compared to untreated. In integrated management, the selected treatments in the nursery and mainfield were evaluated using the resistant variety Sree Dhara. Based on the overall performance in reduction of nematode population (soil and root), the improvement of biometric characters and yield of coleus tubers, integration of soil solarization in nursery for 15 days with 150 guage LDPE film and main field application of P. lilacinus (15 g m-2) in combination with either neem cake (100 g m-2) or B. macerans (15 g m-2) were the best treatments for recommendation in the integrated nematode management strategy in S. rotundifolius. This strategy protected the crop against M. incognita and improved the per ha yield to a tune of 64.33 to 66.18 per cent. In addition to this, by reducing the nematode population in root (97.89 to 99.73 per cent), the quality parameters of tubers like starch, sugar and crude fibre content were also maintained.